Roll Call Votes in the European Parliament: a good sample or a poisoned dead end?. (2nd January 2017) - Kaniok, Petr; Mocek, Ondřej
SUMMARY: The Roll Call Vote (RCV) of Members of the European Parliament is a standard data source for modern research into the European Parliament (EP). RCV samples are used in particular to study political group cohesion and the emergence of conflict lines within the EP. Current mainstream research thus treats RCVs as a reliable source of data. But other research exists that questions the suitability of the RCV as a sample that fairly represents the population of EP votes. Specifically, this latter research stream points to the over-representation of non-legislative items over legislative items and to the under-representation (or even complete absence) of some committees. However, these critically oriented studies focus on data that does not take into account changes that have occurred in recent years, after the Treaties of Nice (2001) and Lisbon (2007) came into force in 2003 (Nice) and 2009 (Lisbon). By analysing all votes that took place in 2013, the authors find that the RCV has become a more reliable data source in recent years. The most important difference – that which obtained between legislative and non-legislative issues – has completely vanished and the remaining differences show only a very weak effect. The authors attribute this change to the empowerment of the EP in the legislative arena and the amendment of the Rules of Procedure.